Study of Molecular Complex Formation between Components, Methanol and Hydrocarbons, in Petroleum Spirit with Dye Indicator— Part-II - Farasram, Rakesh; Farasram, P.L.; Desai, C.M. (Asian Journal of Chemistry, 2010)
Different physical properties of binary organic liquids have been studiedand have shown molecular interaction between two liquids, formingmolecular complex; this concept has been used to study molecular complexformation between organic components methanol and hydrocarbons innonpolar solvent petroleum spirit spectrophotometrically by monovariationmethod using dye indicator.